KEPASTIAN HUKUM AKTA DI BAWAH TANGAN YANG TELAH DILEGALISASI NOTARIS DALAM PEMBUKTIAN DI PENGADILAN - Hengki Pranata; Amelia Nur Widyanti; Iran Sahril (Bajang Institute, 2026)
In civil court proceedings, one of the duties of the judge is to investigate whether or not a legal relationship is the basis of the lawsuit so that in the legal analysis of proof of an underhand deed legalized by a notary, there are differences in the application of an underhand deed by a Notary. According to Article 1874a of the Civil Code and Article 15 paragraph (2) letter a UUJN. These differences cause the Notary in carrying out his position to be different in applying the deed under the hand. The problem in the research, how is the deed under the hand in the law of civil proof, how is the authority of the notary in the procedure for proving the deed under the handAccording to Article 15 paragraph (2) letter a of the UUJN and Article 1874a of the Civil Code, what are the legal consequences of implementing an Underhand Deed in accordance with Article15 paragraph (2) letter a UUJN or Article 1874a of the Civil Code. First Theory ruling that includes theory Answer Ruling menu R.Soeroso and Theory Belief Ruling menu Jan Michiel Otto. Method of including penalty herein with any normative jurisdictional penalty, including primary, secondary and tertiary penalty or secondary data. A combination of peer-reviewed pedagogies ranging from groundbreaking pedagogy, conceptual pedagogy, analytical pedagogy, case pedagogy, and techniques to identifying and inventorying positive pedagogy, literature, books, journals and several pedagogical pedagogies. For technical analysis, judgments are made with grammatical interpretation, systematic interpretation, and judgment construction methods. As a result of the private deed applied by the Notary as referred to in Article 15 paragraph (2) letter a of the UUJN, the deed has the power of formal proof of truth guaranteed by the Notary so that the private deed is not included in the category of weak evidence. As a result of a private deed applied by a Notary as referred to in Article 1874a of the Civil Code, the deed has the power of formal and material proof of truth